INFLUENCE OF ARTIFICIAL INTELLIGENCE UTILIZATION ON STUDENTS’ COGNITIVE ENGAGEMENT AND MOTIVATION TO LEARN (NAU Journal of Technology and Vocational Education, 2026)
The transformation in technology has influenced the educational landscape in schools and universities worldwide. This study investigated the influence of artificial intelligence (AI) utilization on students’ cognitive engagement and motivation to learn, hence the study. Two research questions guided the study and two null hypotheses were tested at 0.05 level of significance. The study employed 222 undergraduate students of Business Education from public universities in Anambra State through a simple random sampling technique. The instrument used for data collection was a structured questionnaire containing 16 items was validated by experts. The data collected were analyzed using Pearson Product Moment Correlation Coefficient to answer research questions and a linear regression to test the hypotheses at 0.05 level of significance using Statistical Package for Social Science (SPSS version 25). The findings of the study revealed that Artificial Intelligence has a moderate positive relationship with cognitive engagement and a positive weak relationship with motivation. The study also revealed that AI utilization significantly influenced Business Education students’ cognitive engagement and motivation to learn. Based on the findings, it was concluded that moderate positive and positive weak correlation respectively could be as a result of inabilities of students to effectively utilize artificial intelligence for learning. The study therefore recommended among others that curriculum developers and institutions should design AI-supported learning experiences that are career-relevant and learner-centered, combining AI tools with real-life c their interest in learning.
Keywords: Artificial Intelligence; Cognitive Engagement; Motivation; Business Education Students